The projection diagram - Muramatsu, Mikaya (2003)
We described a diagram, named the projection diagram (PD), that can be used for the interpretation of fringe projection operations in a similar way as the Holodiagram is used in Holography and others branches in optics. It is obtained a a Moire pattern between two spoke targest that mimic central projections, tha same as those in a projection and observationsystem or two projection sysstem. N. Abramson (Academic, London(1981))was already proposed its use in system with two observation points. By using this PD, several interesting features dealing with fringe projection are highlighted. Information on the sensitivity vector and the geometry of the contouring surface can be straightforwardly obtained in graphical way. The effect of defocusing can also be included in the diagram.